Life in the current: Anatomy and morphology of utricularia neottioides - Płachno, Bartosz J.; Adamec, Lubomír; Świątek, Piotr; Kapusta, Małgorzata; Miranda, Vitor F. O. [UNESP] (MDPI, 2020)
Rheophytism is extremely rare in the Utricularia genus (there are four strictly rheophytic species out of a total of about 260). Utricularia neottioides is an aquatic rheophytic species exclusively growing attached to bedrocks in the South American streams. Utricularia neottioides was considered to be trap-free by some authors, suggesting that it had given up carnivory due to its specific habitat. Our aim was to compare the anatomy of rheophytic U. neottioides with an aquatic Utricularia species with a typical linear monomorphic shoot from the section Utricularia, U. reflexa, which grows in standing or very slowly streaming African waters. Additionally, we compared the immunodetection of cell wall components of both species. Light microscopy, histochemistry, scanning, and transmission electron microscopy were used to address our aims. In U. neottioides, two organ systems can be distinguished: organs (stolons, inflorescence stalk) which possess sclerenchyma and are thus resistant to water currents, and organs without sclerenchyma (leaf-like shoots), which are submissive to the water streaming/movement. Due to life in the turbulent habitat, U. neottioides evolved specific characters including an anchor system with stolons, which have asymmetric structures, sclerenchyma and they form adhesive trichomes on the ventral side. This anchor stolon system performs additional multiple functions including photosynthesis, nutrient storage, vegetative reproduction. In contrast with typical aquatic Utricularia species from the section Utricularia growing in standing waters, U. neottioides stems have a well-developed sclerenchyma system lacking large gas spaces. Plants produce numerous traps, so they should still be treated as a fully carnivorous plant.
Keywords: Aquatic plants; Carnivorous plants; Cell-wall components; Cerrado; Lentibulariaceae; Plant anatomy; Rheophytes